Implementing Research-Based Learning in Statistics and Probability Topics: A Workshop for Mathematics Teachers in Developing Contextual Inquiry Projects - Sundayana, Rostina; Wartini, Tini; Usman, Ali; Nurbani, Tri; Firmansyah, Hilman; Lisna, Yusi Yusnita Juwita; Amirah, Eva; Masripah, Imas Siti; Nuryadin, Rully; Suryadi, Yopi; Hilman, Shinta Indriawati; Fajar, Pipih Nurul; Solihat, Deti Farida; Sari, Maya; Kusumah, Reni Risnawati (Fakultas Kewirausahaan Universitas Garut, 2024)
Mathematics education in Indonesia faces challenges in statistics and probability, often taught procedurally, leading to low student motivation and limited critical thinking. Teachers also struggle with scarce resources and outdated methods. Research-Based Learning (RBL) is proposed as an urgent solution, aligning with the Merdeka Curriculum, encouraging students to engage in the scientific process for deeper understanding. This community engagement initiative implemented RBL in statistics and probability for mathematics teachers in Garut Regency through a participatory teacher professional development approach. The workshop, based on the PPDAC framework, involved 30 teachers, training them to design contextual inquiry projects and analyze data using spreadsheets. A pre-assessment identified a competency gap, but post-assessment showed a 21% increase in teachers' understanding of RBL and statistics, along with improved confidence in project design. The program successfully enhanced teachers' technical competencies in teaching statistics innovatively, directly impacting the quality of learning in schools.